At‑Tijārah al‑Mubīqah (Destructive Business and Trade): Qurʾān, Ḥadīth, Qawā‘id al-Fiqhiyyah and Maqāṣid al-Sharī‘ah Perspective - Muhammad Fauzi; Al Mahdi; Arzam Arzam; Mursal Mursal (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study aims to analyse and formulate a conceptual framework of at‑tijārah al‑mubīqah based on the perspectives of the Qurʾān, ḥadīth al‑sabʿu al‑mubīqāt, qawāʿid al‑fiqhiyyah, and maqāṣid al‑sharīʿah. Three research questions are addressed: (1) what is the conceptual definition of at‑tijārah al‑mubīqah, and how does it differ from ideal business and trade when viewed through the Qurʾān, ḥadīth, qawāʿid al‑fiqhiyyah, and maqāṣid al‑sharīʿah, with ḥadīth al‑sabʿu al‑mubīqāt as the main normative framework; (2) how can the manifestations of ḥadīth al‑sabʿu al‑mubīqāt be identified and explained as forms of at‑tijārah al‑mubīqah in the modern context through the analysis of qawāʿid al‑fiqhiyyah and the assessment of their impact on maqāṣid al‑sharīʿah; and (3) how can an integrated conceptual framework of at‑tijārah al‑mubīqah be constructed and function as a normative reference for contemporary business practice. This study employs a qualitative approach through library research, using a normative‑descriptive and analytical‑conceptual design. Data are collected from primary sources and reinforced by secondary sources, and analysed using content analysis combined with tafsīr mauḍūʿī, qawāʿid al‑fiqhiyyah, and maqāṣid al‑sharīʿah as analytical tools. The study shows that at‑tijārah al‑mubīqah encompasses all tijārah activities that contain one or more elements of ḥadīth al‑sabʿu al‑mubīqāt, identified through qawāʿid al‑fiqhiyyah as ḍarar that must be eliminated, and that substantially damage maqāṣid al‑sharīʿah at a significant, widespread, and sustained level. Seven main manifestations are identified in the modern business ecosystem: shirk, magic (siḥr), structural soul murder, ribā, consuming the wealth of orphans, betrayal of trust (amānah), and fitnah against the honour of Muslim women. To the best of the author’s knowledge, this is the first study to systematically construct at‑tijārah al‑mubīqah as a formal academic taxonomy in Islamic business ethics explicitly derived from ḥadīth al‑sabʿu al‑mubīqāt, while simultaneously integrating qawāʿid al‑fiqhiyyah and maqāṣid al‑sharīʿah into a single four‑layer conceptual framework. The study offers a novel reading, particularly of three categories of al‑mubīqāt in the landscape of modern business: the ḥadīth phrase “killing a soul is forbidden by Allah Subḥānahu Wa Taʿālā, except with ḥaq” is positioned as structural soul murder; the prohibition of “fleeing from the battlefield” is read as betrayal of trust (amānah); and “accusing a chaste Muslim woman of adultery (qadzaf)” is interpreted as fitnah against the honour of Muslim women. Accordingly, this study not only broadens the conceptual discourse but also enriches the ethical‑empirical mapping of destructive patterns within contemporary business ecosystems